Observation of the Fulde-Ferrell-Larkin-Ovchinnikov state in the quasi-two-dimensional organic superconductor κ-(BEDT-TTF)2Cu(NCS)2 (BEDT-TTF≡bis(ethylene-dithio)tetrathiafulvalene) - Singleton, J; Symington, J; Nam, M; Ardavan, A; Kurmoo, M; Day, P (IOP, 2000)
Single crystals of the quasi-two-dimensional organic type II superconductor, κ-(BEDT-TTF)2Cu(NCS)2, have been studied in magnetic fields of up to 33 T and at temperatures between 0.5 K and 11 K using a compact differential susceptometer. When the magnetic field lies precisely in the quasi-two-dimensional planes of the material, there is strong evidence for a phase transition from the superconducting mixed state into a Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state, manifested as a change in the rigidity of the vortex system. The behaviour of the transition as a function of temperature is in good agreement with theoretical predictions.